PENINGKATAN PENGETAHUAN DAN KETERAMPILAN DIGITAL MARKETING BAGI SISWA SMK YPE KROYA - Wibowo, Fajar Nur; Farkhah, Laeli; Janah, Anggita Raudhatul; Rizkya, Dayna (ICON Publisher, 2025)
This community service program aims to improve vocational school students' digital marketing knowledge and skills at SMK YPE Kroya in Cilacap Regency. Training and mentoring were conducted to provide an understanding of digital marketing and its application strategies in business. The activity results showed that participants gained a better understanding of the benefits of digital marketing, both in terms of the environment and business competitiveness. Continuous mentoring and support from the government and academia are necessary to make skill development for vocational high school students more effective. Digital marketing is one of the strategies proposed to improve the performance of SMEs. This program positively prepares the younger generation to become millennial entrepreneurs capable of building a sustainable business ecosystem for SMEs in Cilacap Regency. Further evaluation is still needed to measure the long-term impact of this knowledge and digital marketing skills enhancement activity.